2007
DOI: 10.2174/187443700100101001
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Keratinized Oral Mucosa Decreased C. albicans Transition Through the Production of Keratins 10, 14, 16, and 19 by Oral Epithelial Cells

Abstract: Abstract:The aim of this study was to evaluate the link between Candida albicans growth and dimorphism and the production of keratins by oral epithelial cells. Various culture models (monolayer and non-keratinized and keratinized engineered human oral mucosa) were produced and used for this purpose. Cell morphology, tissue structure, and the transition of C. albicans were assessed following cell and tissue infections. Keratin production by epithelial cells exposed to C. albicans was evaluated by Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The effects of this quorum sensing molecule are indeed associated with the inhibition of filamentation and the promotion of planktonic yeasts [ 25 ]. While Candida-enhanced secretion of farnesol and tyrosol may have partially contributed to the observed effects, another input was probably provided directly by HSCO and HECV cells, a possibility that would fit a number of reports dealing with the interaction of C. albicans with epithelial and endothelial cells [ 26 , 27 ]. Although many uncertainties remain on the cellular components and pathways involved in this interaction, in fact, there is a general consensus that the encounter with Candida species stimulates epithelial and endothelial cells to internalize the organism by endocytosis, a process widely regarded as an important step in the defense system mounted by the host [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of this quorum sensing molecule are indeed associated with the inhibition of filamentation and the promotion of planktonic yeasts [ 25 ]. While Candida-enhanced secretion of farnesol and tyrosol may have partially contributed to the observed effects, another input was probably provided directly by HSCO and HECV cells, a possibility that would fit a number of reports dealing with the interaction of C. albicans with epithelial and endothelial cells [ 26 , 27 ]. Although many uncertainties remain on the cellular components and pathways involved in this interaction, in fact, there is a general consensus that the encounter with Candida species stimulates epithelial and endothelial cells to internalize the organism by endocytosis, a process widely regarded as an important step in the defense system mounted by the host [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, this method is not useful for viable but nonculturable organisms. 24,30,36,54 Alternative methods like crystal violet staining and resazurin staining can be used for biofilm research. 88 Five studies used confocal laser scanning microscopy (CLSM) to investigate various aspects of microbial biofilm formation.…”
Section: Methods Of Evaluation Of Infected Ommmentioning
confidence: 99%
“…30 Yeast transition is reduced in keratinized form of oral mucosa in comparison to nonkeratinized form. 36 Although Samaranayake et al reported no penetration of C. albicans into the connective tissue layer at 48 h, 35 Whiley et al and Dongari-Bagtzoglou and Kashleva showed that penetration into the submucosa was dependent on the strain used for infection. 7,34 Association of C. albicans with other microorganisms, like Staphylococcus aureus or S. oralis, could result in deeper invasion into subepithelial collagen matrix.…”
Section: Survival and Penetration Of Microorganism In Oral Mucosa Modelmentioning
confidence: 99%
See 1 more Smart Citation